Probabilistic bulk production cost model by a continuation Monte Carlo simulation method - Rivier Abbad, Michel Luis; Pérez Arriaga, José Ignacio (Sin editorial (Londres, Reino Unido), 2002)
No disponibleNot available

No disponibleNot available
Capítulos en libros
Keywords: Instituto de Investigación Tecnológica (IIT)